2003
DOI: 10.1002/mar.10076
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual model of perceived customer value in e‐commerce: A preliminary investigation

Abstract: This article presents an exploratory study of a conceptual model of perceived customer value in a business-to-consumer e-commerce setting. Key precursors of perceived customer value included in the model are valence of on-line shopping experience, perceived product quality, perceived risk, and product price. Relationships among these variables (as well as mediating variables) and their relationship to on-line shoppers' value perceptions are explored. The theoretical framework proposed in this work expands on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
461
2
29

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 781 publications
(554 citation statements)
references
References 65 publications
(120 reference statements)
24
461
2
29
Order By: Relevance
“…Past studies have often considered perceived risk to be an antecedent of perceived value [16,43]. Research by Agarwal and Teas (2001) [44] showed that the perceived risk plays an important role in forming consumers' perceptions of value.…”
Section: Relationship Between Perceived Risk and Valuementioning
confidence: 99%
“…Past studies have often considered perceived risk to be an antecedent of perceived value [16,43]. Research by Agarwal and Teas (2001) [44] showed that the perceived risk plays an important role in forming consumers' perceptions of value.…”
Section: Relationship Between Perceived Risk and Valuementioning
confidence: 99%
“…Engel, Blackwell and Miniard (2001) considered that perceived value indicates the difference between the time, money, physical strength, and other resources that consumers pay for a product as well as the benefits that the consumers obtain. Chen and Dubinsky (2003) addressed that perceived value results from the sum of trade cost as well as the value of expected benefits or loss. According to Ravald and Gronroos (1996), the concept of consumer value has become a differentiation tool and one of the critical factors to maintain corporate predominance in competition.…”
Section: Literature Review Product Design Featuresmentioning
confidence: 99%
“…Some authors have studied value in the context before the purchase (Chen, Dubinsky 2003;Monroe 1990), during the purchase (Holbrook 1999;McDougall, Levesque 2000;Ulaga, Chacour 2001) and at different times during the purchase decision process ( Van der Haar et al 2001;Woodruff 1997). This phenomenon reflects the dynamic nature of the concept (Sánchez, Iniesta 2006).…”
Section: Perceived Value (Pv)mentioning
confidence: 99%